Tackling misconceptions in primary mathematics : preventing, identifying and addressing children's errors - Mackle, Kieran (London : Routledge, 2017)
Did you know that a circle has more than one side? Are you aware of the difference between 1:2 and ư? Could you spot when a 2D shape is actually 3D? Tackling Misconceptions in Primary Mathematics is a practical guide based on the principles that sound subject knowledge is key to fostering understanding, and addressing misconceptions is central to pupil progress. With an emphasis on preventing as well as unpicking misconceptions in the classroom, it offers trainee and practising teachers clear explanations, practical strategies, and examples of the classroom language and dialogue that will help pupils successfully navigate tricky topics. The book demonstrates the importance of preventing misconceptions through what is said, done and presented to children, giving a variety of examples of common misconceptions and exploring how they can be addressed in a classroom environment. Proper intervention at the point of misconception is regarded as a key skill for any outstanding classroom practitioner and the author stresses the value in understanding how the pupil got there and explaining that it's okay to make mistakes. Misconceptions are only one step away from correctly formed concepts if harnessed with care and skill. This comprehensive text is designed to be read as either a short course introduction, or dipped into as a guide to assist teaching. It is essential reading for trainee primary school teachers on all routes to QTS, as well as mathematics subject leaders and practising teachers looking to inspire the next generation of confident and inquisitive mathematicians.
Includes bibliographical references.
Keywords: Mathematics -- Study and teaching -- United States